Are Vietnamese coffee farmers willing to pay for weather index insurance? - Le Ngoc, Lan; Mushtaq, Shahbaz; Wang, Qingxia (Jenny); Barlis, Angelica; Deniau, Aline; Byrareddy, Vivekananda Mittahalli; Anh, Huynh Tan; Swaans, Kees (Elsevier, 2024)
Global coffee production experiences detrimental impacts of climate change. Weather index insurance (WII) offers an opportunity for coffee farmers to mitigate the climate risks in production and motivate them to adopt sustainable farming practices. This study explores Vietnamese farmers' willingness to participate and pay for WII schemes for coffee. A contingent valuation survey was employed on a sample of 151 farmers from the two largest coffee production areas: Lam Dong and Dak Lak provinces. The findings revealed that farmers are willing to pay, on average, US$92.30 per policy for a premium on insurance products. We also found that farmers in Lam Dong are willing to pay more than those in Dak Lak despite fewer Lam Dong farmers being willing to participate in the insurance schemes. The majority of farmers prefer drought to be insured within 3 months of coffee blossom, from February to April. Factors influencing farmers' decision to join the insurance schemes include education, farm size, climate change perception and experiences, and insurance knowledge. The study suggests that the current coffee industry co-contribution to insurance premiums could potentially be reduced by up to 90 %. However, caution must be taken when adjusting co-contribution, as farmers' willingness to pay is heterogeneous. In addition, raising awareness of the impact of climate change on crop production and insurance knowledge training is critical to ensure an increased number of participants in the schemes. The recommendations from this study will contribute to improving the design of coffee insurance products that are tailored to local needs and preferences and will assist in upscaling the products' outreach in the Coffee Climate Protection Insurance Program.